2022
DOI: 10.21154/joipad.v2i2.4831
|View full text |Cite
|
Sign up to set email alerts
|

Zakat Program for Post-Pandemic Economic Recovery: Qualitative Approach using Nvivo

Abstract: Introduction/Main Objectives: This study aims to determine the development of research related to the practice of zakat a program for restoring the economy, where zakat is one of the Islamic financial instruments that can break the chain of poverty and build prosperity. Background Problems: The global economic crisis due to COVID-19 has caused concern for the world. Not only that, Covid-19 caused an increased number of mustahik because people have lost their jobs. Novelty: The zakat program can be used solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, a graphical depiction of the sentiment derived from the auto-coded sentiment is displayed with objective results. Some of Nvivo's applications in Islamic economic and financial research can be seen in the studies conducted by Izza (2021), Izza et al, (2021), also Sunarya & Rusydiana (2022a, 2022b. Furthermore, this section describes the publication of articles by the journal.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a graphical depiction of the sentiment derived from the auto-coded sentiment is displayed with objective results. Some of Nvivo's applications in Islamic economic and financial research can be seen in the studies conducted by Izza (2021), Izza et al, (2021), also Sunarya & Rusydiana (2022a, 2022b. Furthermore, this section describes the publication of articles by the journal.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, another advantage of using NVivo 12 Plus is that it can collect, organize, analyze, and visualize unstructured or semi-structured data by importing data in various file formats, organizing demographic data, source code, capturing ideas, running queries, and visualizing project items (Izza & Rusydiana, 2022). Research using Nvivo for SLR analysis in Islamic economics topic can be found at Izza & Mi'raj (2023), Izza et al, (2021), and also Sunarya & Rusydiana (2022).…”
Section: Methodsmentioning
confidence: 99%
“…NVivo analysis can be used to find out and visualize keywords, research developments or research topics on a topic, which in this study is zakat management in Indonesia. A number of studies relevant to this research include Sunarya & Rusydiana (2022) examining the development of research related to the practice of zakat economic recovery programs, where zakat is one of the Islamic financial instruments that can break the chain of poverty and build welfare. The results showed an increasing trend of research related to zakat as one of the financing instruments in Islamic economics.…”
Section: Introductionmentioning
confidence: 99%